Niska cena jako narzędzie kreowania przewagi konkurencyjnej - Waniowski, Paweł (The Low Price as a Tool in Creating Competitive Advantage, 2007)
The price competition is one of the basic ways of creating competitive advantage. On the Polish market it has the special meaning for a high price elasticity of demand in many lines and very intensive competition. These factors cause that the price competition on the Polish market is very high. This article presents also the rules of the price competition and many examples of the low price applications both by chain stores and on local markets.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1170, s. 146-155